APPLICATION OF METHODS OF INCREASING THE QUANTITY OF FIBER OUTPUT DURING THE PROCESS OF SPINNING - Abzoirov Ortiq Xonimkulovich; Kushimov Azamat Abdurazzakovich; Xolmatov Shaxzod; Xolmatov Javoxir; Apurba Das (Galaxy International Interdisciplinary Research Journal, 2024)
In the process of separating the seeds, the raw material formed in the working chamber of the gin depends on the composition of the roller. This is due to the fact that the teeth of the rotating saw grab the fiber, attach the cotton to its back and make the roller with the raw material rotate, and the process of separating the seeds takes place in the working chamber.